Design of stem separator tool with Cyclea Barbata (Cincau) plant leaves to increase business productivity of Sunter Jaya Residents of Jakarta Utara - Yunus, Ahmad; Kurniaty, Ika; Sari, Fatma; Prasetyawati, Meri; Chamdareno, Prian Gagani; Kurnianto, Tri (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2020)
Cincau (Cyclea barbata) is a plant whose leaves can be squeezed thick for the contents of a drink. This plant is a species of the cyclea genus. Green grass jelly leaves are found in various places in Indonesia, from traditional markets to modern shopping centers. This plant is known as camcao (Javanese), camcauh (Sundanese), juju, kepleng, krotok, tarawalu, tahulu (Malay). There are several types of grass jelly known today, namely green grass jelly, black grass jelly, and oil grass jelly. Indonesian people are fond of green grass jelly because the physical nature of green grass jelly leaves (Cyclea barbata) is thin and limp so that it is easier to form into gelatin or into gelatin. So far, research that examines quality improvement in the processing process has not been given much attention, because many think that the process currently carried out meets the standards. For this reason, through this research, efforts were made to improve the quality of Cyclea barbata leaves through the initial stages of the Cyclea barbata leaf processing process. The stalks and leaves of the henna must be separated from the beginning of the processing process before being processed further, so that the pure processed material comes from Cyclea barbata leaves which produce the best Cyclea barbata leaf powder, so that it is expected to produce quality Cyclea barbata leaf products. For that we need a separator for the leaves and stems of the Cyclea barbata plant. This research is needed to produce a design for separating the stem and leaves of the Cyclea barbata plant. The design of this tool needs to refer to the physical characteristics of the leaves and stems of the Cyclea barbata plant, so that power requirements are reduced and operational costs decrease.